Correspondence Analysis between Me Too Drugs Formulation with Patent Information and the Analytical Method (Case Study: Amlodipine Tablets - PT Indofarma (PERSERO) Tbk.) - Fetrikani Andartaji; Gede Bayu Suparta; Marchaban Marchaban (Faculty of Pharmacy, Universitas Gadjah Mada)
One of the blockbuster drugs that has been off-patent and attract domestic pharmaceutical industry to produce a lot of version of me too is anti-hypertensive drugs Norvask®, in which the active ingredient is the salt form of amlodipine besylate. The goal of this study is to verify the conformity between me too drugs formulation and patent information (Case study: Amlodipine Tablets – PT Indofarma (Persero) Tbk). The results are expected to change the views of people who often doubt that me too drugs quality are smaller than patent drugs. The analysis method used in this study is performed descriptively. Information about amlodipine formulation obtained from PT Indofarma (Persero) Tbk is verified with the active substance test results obtained from amlodipine drugs on the market. After that, the total results can be compared with the proprietary patent information obtained from United States Patent and Trademark Office (USPTO) website. The result showed that there is a compatibilty between formulation of me too drugs and patent information (Case Study: Amlodipine – PT Indofarma (Persero) Tbk) in major issues such as compotition, active ingredient, level of active ingredient, dosage form and production process. Profile dissolution which is owned by amlodipine tablet from PT Indofarma (Persero) Tbk remains equivalent to the innovator product (Norvask®), although there was a modification by adding an excipient X. Amlodipine tablet generic produced by PT Indofarma (Persero) Tbk is me too 100% (identical).